Impact of greenhouse gas metrics on the quantification of agricultural emissions and farm-scale mitigation strategies: a New Zealand case study - Reisinger, Andy; Ledgard, Stewart (IOP Publishing, 2013)
Agriculture emits a range of greenhouse gases. Greenhouse gas metrics allow emissions of different gases to be reported in a common unit called CO2-equivalent. This enables comparisons of the efficiency of different farms and production systems and of alternative mitigation strategies across all gases. The standard metric is the 100 year global warming potential (GWP), but alternative metrics have been proposed and could result in very different CO2-equivalent emissions, particularly for CH4. While significant effort has been made to reduce uncertainties in emissions estimates of individual gases, little effort has been spent on evaluating the implications of alternative metrics on overall agricultural emissions profiles and mitigation strategies. Here we assess, for a selection of New Zealand dairy farms, the effect of two alternative metrics (100 yr GWP and global temperature change potentials, GTP) on farm-scale emissions and apparent efficiency and cost effectiveness of alternative mitigation strategies. We find that alternative metrics significantly change the balance between CH4 and N2O; in some cases, alternative metrics even determine whether a specific management option would reduce or increase net farm-level emissions or emissions intensity. However, the relative ranking of different farms by profitability or emissions intensity, and the ranking of the most cost-effective mitigation options for each farm, are relatively unaffected by the metric. We conclude that alternative metrics would change the perceived significance of individual gases from agriculture and the overall cost to farmers if a price were applied to agricultural emissions, but the economically most effective response strategies are unaffected by the choice of metric.